2008
DOI: 10.1007/s00268-008-9535-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Stage IV Colorectal Cancer and Prognosis

Abstract: Our results suggested that the most dismal CRC harbors three definite vectors that may represent the strongest phenotype of putative systemic immune (CA19-9), distant metastasis (extent of liver metastases), and local progression (peritoneal dissemination).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 39 publications
1
42
2
2
Order By: Relevance
“…High levels of serum CEA on diagnosis has been associated with a poor prognosis in some studies, while others have found no significant correlation between CEA and prognosis (Stelzner et al, 2005;Katoh et al, 2008;Wen-Zhuo et al, 2014). The increase of CA 19-9 has demonstrated a significantly higher frequency of metastasis and distinctly lower survival rate, making it an adverse prognostic factor for CRC patients (Katoh et al, 2008;Levy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of serum CEA on diagnosis has been associated with a poor prognosis in some studies, while others have found no significant correlation between CEA and prognosis (Stelzner et al, 2005;Katoh et al, 2008;Wen-Zhuo et al, 2014). The increase of CA 19-9 has demonstrated a significantly higher frequency of metastasis and distinctly lower survival rate, making it an adverse prognostic factor for CRC patients (Katoh et al, 2008;Levy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of CA 19-9 has demonstrated a significantly higher frequency of metastasis and distinctly lower survival rate, making it an adverse prognostic factor for CRC patients (Katoh et al, 2008;Levy et al, 2008). Katoh et al assessed the prognostic significance of elevated serum CA 19-9 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased survival might be explained by a difference in indication for blood transfusion or anatomic site studied, or because of the few confounding factors taken into account (preoperative hemoglobin, age, sex, Tokuhashi score [survival prognostication score], and number of instrumented levels) [7]. Previous studies in visceral metastatic disease have shown a negative effect of perioperative blood transfusion on survival [14,16]: Katoh et al [14] found that perioperative transfusion was independently associated with worse survival after resection of stage IV (disseminated disease) colorectal cancer (n = 162) after accounting for clinical and treatment parameters; Margulis et al [16] reported that survival of patients undergoing cytoreductive nephrectomy for metastatic renal cell carcinoma also was negatively influenced by intraoperative blood transfusion. The decrease in observed survival after perioperative blood transfusions in primary malignancies was not apparent in our study on metastatic long-bone fractures and might be explained by the already widely disseminated disease and poor overall survival, potentially attenuating the effect of blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Both synchronic metastasis and bowel obstruction are considered poor prognosis factors as well as high preoperative levels of CA 19.9, histological grade, extension of liver metastasis or peritoneal metastases. 2,5,6 Resection of the primary tumour has been claimed to improve survival 7,8 but it has also been suggested that adding a surgical aggression to palliative patients with high volume disease may lead to high morbidity and mortality. The American Society of Clinical Oncology (ASCO) does not recommend resection of stage IV CRC in asymptomatic patients unless an intention to cure strategy is planned or when at risk of obstruction.…”
Section: Introductionmentioning
confidence: 99%